Electrostatic catalysis of a Diels-Alder reaction - Aragonès, A.; Haworth, N.; Darwish, Nadim; Ciampi, S.; Bloomfield, N.; Wallace, G.; Diez-Perez, I.; Coote, M. (Nature Publishing Group, 2016)
It is often thought that the ability to control reaction rates with an applied electrical potential gradient is unique to redox systems. However, recent theoretical studies suggest that oriented electric fields could affect the outcomes of a range of chemical reactions, regardless of whether a redox system is involved. This possibility arises because many formally covalent species can be stabilized via minor charge-separated resonance contributors. When an applied electric field is aligned in such a way as to electrostatically stabilize one of these minor forms, the degree of resonance increases, resulting in the overall stabilization of the molecule or transition state. This means that it should be possible to manipulate the kinetics and thermodynamics of non-redox processes using an external electric field, as long as the orientation of the approaching reactants with respect to the field stimulus can be controlled. Here, we provide experimental evidence that the formation of carbon-carbon bonds is accelerated by an electric field. We have designed a surface model system to probe the Diels-Alder reaction, and coupled it with a scanning tunnelling microscopy break-junction approach. This technique, performed at the single-molecule level, is perfectly suited to deliver an electric-field stimulus across approaching reactants. We find a fivefold increase in the frequency of formation of single-molecule junctions, resulting from the reaction that occurs when the electric field is present and aligned so as to favour electron flow from the dienophile to the diene. Our results are qualitatively consistent with those predicted by quantum-chemical calculations in a theoretical model of this system, and herald a new approach to chemical catalysis.